Swedish evidence on the impact of cognitive and non-cognitive ability on earnings: An extended pre-market factor approach - Johnny Zetterberg (Institute for Labour Market Policy Evaluation (IFAU), 2005)
This paper investigates the impact on earnings of non-cognitive ability, measured in terms of individuals' 'self-esteem' on earnings. Starting with the pre-market factor approach suggested by Neal & Johnson (1996) a main finding is that measures of relative self-esteem along with cognitive ability are positively correlated with earnings. The analysis also reveals that the returns to cognitive and non-cognitive ability vary over the earnings-distribution: the returns are larger at higher levels of earnings than at low levels. While qualitatively robust, the effects decrease in magnitude when an extended version of the pre-market factor model is used.
Keywords: J31; M54; 330; Incentive-influencing preferences; cognitive ability; non-cognitive ability; relative and absolute self-esteem; earnings distribution; Lohnstruktur; Sozialpsychologie; Kognition